2000
DOI: 10.1007/s004390000343
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure of a copy of the human TPTE gene which encompasses 87 kb on the short arm of chromosome 21

Abstract: The testis-expressed human TPTE is a putative transmembrane tyrosine phosphatase, probably involved in signal transduction pathways of the endocrine and/or the spermatogenetic function of the testis. TPTE was mapped to the pericentromeric region of human chromosomes 21 and 13, and to chromosomes 15, 22, and Y. It is unknown which of the TPTE copies are transcribed, contain intronic sequences, and/or have open reading frames. Here, in silico analysis of the genomic sequence of human chromosome 21 allowed the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Analysis of the human genome draft sequence confirmed that TPTE maps to the short arm of chromosome 21 (GenBank Hs21 _ 29649, band 21p11.2) (Guipponi et al, 2000). Supplementary TPTE copies map to Hsa13, Hsa15, Hsa22 and the HsaY (Chen et al, 1999).…”
Section: Introductionmentioning
confidence: 76%
“…Analysis of the human genome draft sequence confirmed that TPTE maps to the short arm of chromosome 21 (GenBank Hs21 _ 29649, band 21p11.2) (Guipponi et al, 2000). Supplementary TPTE copies map to Hsa13, Hsa15, Hsa22 and the HsaY (Chen et al, 1999).…”
Section: Introductionmentioning
confidence: 76%
“…For acrocentric chromosomes, this organization might be important for the correct expression of ribosomal genes or for genesthat are yet to be identified and that are located on the short arms. In this regard, a protein-coding gene (a putative tyrosine phosphatase) has recently been assigned to 21p for the first time (Hattori et al 2000;Guipponi et al 2000). In addition to the knowledge derived from the partial sequence characterization of chromosomes 22p and 21p (Shiels et al 1997;Hattori et al 2000), this work provides new information concerning the sequence organization of the p-arm of acrocentric chromosomes and particularly on their paralogous nature.…”
Section: Discussionmentioning
confidence: 93%
“…Secondly, genes do exist in repeat regions. The gene TPTE was found on the acrocentric arm of chromosome 21 (Chen et al, 1999; Guipponi et al, 2000; Eichler et al, 2004). Many RefGenes are located in the 1 kb-unmappable regions in the assembled reference human genome (Li and Freudenberg, 2014; Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%